Gestão do cuidado na atenção primária frente à tuberculose: discurso de enfermeiros sobre registros emprontuários - Januário, Dilyane Cabral (2023)
Introduction: Nursing care management involves tools such as records and critical thinking that leads to the idea of “doing nursing” different from reductionist and fragmented thinking. The nurse's record is an important organizational arrangement that supports the organization of health actions, essential to aid in decision-making, legal registration of elaborated care, source of clinical data, shared interprofessional communication, in addition to supporting research. Thus, understanding the experiences regarding the records of nurses in the care of people with tuberculosis in Primary Health Care is paramount, as it will contribute to the production of health indicators, with a view to achieving the goals established by the World Health Organization in search of of tuberculosis eradication. Objective: To analyze the discourses of nurses on aspects related to records in medical records for the management of care for people with tuberculosis in Primary Health Care. Method: Study with a qualitative approach, with theoretical and methodological support of Discourse Analysis, of French origin. The study was carried out with nurses from the Family Health Units, in the city of João Pessoa, Paraíba, Brazil. Data collection was carried out from June to September 2022 with 31 nurses. The organization of the empirical material took place in the Atlas.ti 9 software and based on the theoreticalmethodological contribution of French Discourse Analysis. The project was approved under opinion number 5,382,492, with CAAE nº 56532822200005188. Results: In total, 31 nurses were interviewed, whose predominant age group for these professionals was between 31 and 40 years, of which 28 were female, where 16 have been working in Primary Care for more than 10 years and 24 claimed to be service providers, with only 4 having other employment relationships for the final analysis. From the corpus, discursive blocks related to the records of clinical aspects in the care of people with tuberculosis in primary care were identified: records and follow-up of treatment of clinical and therapeutic tuberculosis cases, focus on treatment, hospital-centered model, active search for contacts ; in addition to discursive blocks related to the records of social aspects related to the treatment of people with tuberculosis in primary care: monitoring of directly observed treatment, recording of food, social incentive, stigmatization and prejudice, and treatment abandonment. Conclusion: The findings showed through the nurses' speeches that the records happen proactively in the TB book, medical records and compulsory notification, therefore these records happen in an unsatisfactory way, with difficulties in filling them out, providing a reflection regarding the importance of the completeness of records, in a reliable, complete, coherent and adequate manner, aiming at the quality of these documents for continuity of care, better decision-making, teaching and research.